Dinamika Lembaga Pendidikan Mempertahankan Eksistensi Pada Era Kompetitif - Qori Kartika (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2017)
This article aims to reveal and reinforce the importance of educational institutions in maintaining their existence. This period, the number of emerging new educational institutions with new concepts and approaches they offer. This makes the old educational institution faced with a critical position, if it does not adapt to the demands of the environment. This article uses a literature study to examine the issues of educational institutional measures to deeply retain existence. The results of the study show that such rapid environmental changes can no longer be overcome by the natural processes of institutional development and